Experimental and numerical study of the behavior of epoxy foam‐filled 3D woven spacer composites under bending load. Issue 5 (14th March 2022) - Zheng, Liangang; Xiao, Yuanxin; Liu, Li; Xu, Fujun
Abstract: In this work, three‐dimensional woven spacer glass fiber/epoxy composites (3DWSC) and epoxy foam‐filled three‐dimensional woven spacer composites (FF‐3DWSC) were prepared, and the behavior of the two composites under bending load was investigated experimentally and numerically. The results show that compared with 3DWSC, FF‐3DWSC displayed a higher bending strength of 134.30 MPa and superior bending stiffness of 9.48 × 10 6 N·mm 2, which was attributed to the synergistic effect of the foam and the skeleton. And unlike the serious damage caused by the significant stress concentration in 3DWSC under bending load, less damage appeared in FF‐3DWSC because the stress was dispersed by the efficient transmission of the load between foam and column yarns. Besides, there was no delamination between the foam and the skeleton after the bending test, indicating the excellent integrated structure of FF‐3DWSC. In addition, the bending behavior of 3DWSC and FF‐3DWSC was simulated on the macro‐scale model by HyperMesh and HyperView. As a result, the finite element analysis results were in close agreement with the experimental results, demonstrating the finite element simulation method proposed here is capable of being used in replacing time‐consuming experiments to study the bending properties of such 3D composites. Abstract :